- 35m
^{2}+16m-3=0

10n^{2}+136n-56=0m<nm<=nm>nm>=nthe relation cannot be determinedOption E

35m^{2}+16m-3=0

35m^{2}-5m+ 21m-3=0

5m(7m -1) + 3(7m -1)=0

(7m-1) ( 5m+3)=0

m= 1/7 , -3/5

10n^{2}+136n-56=0

10n^{2}-4n+ 140n -56=0

n( 10n-4) + 14(10n-4)=0

(10n-4) ( n+14)=0

n= 4/10,- 14

Hence the relation cannot be determined - 10m
^{2}-136m-14=0

25n^{2}-10n-8=0m<nm<=nm>nm>=nthe relation cannot be determinedOption C

10m^{2}-136m-14=0

10m^{2}-140m+m-14=0

10m(m -14) + 1(m -14)=0

(m-14) ( 10m+1)=0

m= +14 , -1/10

25n^{2}-10n-8=0

25n^{2}-20n+ 10n -8=0

5n( 5n-4) + 2(5n-4)=0

(5n-4) ( 5n+2)=0

n= 5/4, -2/5

Hence m>n - 11m
^{2}+120m= 11

8n^{2}+74n+143=0m<nm<=nm>nm>=nthe relation cannot be determinedOption E

11m^{2}+120m= 11

11m^{2}+121m-m-11=0

11m(m +11) -1(m +11)=0

(m+11) ( 11m-1)=0

m=- 11 , 1/11

8n^{2}+74n+143=0

8n^{2}+22n+52n+143 =

2n( 4n+11) +13(4n+11)=0

(4n+11) ( 2n+13)=0

n= -11/4, -13/2

Hence the relation cannot be determined - 8m
^{2}+51m+18=0

49n^{2}-1=0m<nm<=nm>nm>=nthe relation cannot be determinedOption A

8m^{2}+51m+18=0

8m^{2}+48m+3m+18=0

8m(m +6) + 3(m +6)=0

(m+6) ( 8m+3)=0

m= -6 , -3/8

49n^{2}-1=0

(7n-1) ( 7n+1)=0

n= 1/7, -1/7

Hence n>m - 40m
^{2}-13m+1=0

18n^{2}+77n-18=0m<nm<=nm>nm>=nthe relation cannot be determinedOption D

40m^{2}-13m+1=0

40m^{2}-8m-5m+1=0

8m(5m -1) -1(5m -1)=0

(5m-1) ( 8m-1)=0

m= 1/5 , 1/8

18n^{2}+77n-18=0

18n^{2}+81n- 4n -18=0

9n( 2n+9) – 2(2n+9)=0

(2n+9) ( 9n-2)=0

n= -9/2, 2/9

Hence m â‰¥ n - 16m
^{2}+60m+14=0

8n^{2}– 77n-30=0m<nm<=nm>nm>=nthe relation cannot be determinedOption A

16m^{2}+60m+14=0

16m^{2}+ 56m+ 4m+14=0

8m(2m +7) + 2(2m +7)=0

(2m+7) ( 8m+2)=0

m= -7/2 , -2/8

8n^{2}– 77n-30=0

8n^{2}-80n+ 3n -30=0

8n( n-10) + 3(n-10)=0

(n-10) ( 8n+3)=0

n= 10, -3/8

Hence n>m - 35m
^{2}+32m+5=0

9n^{2}– 36n+32=0m<nm<=nm>nm>=nthe relation cannot be determinedOption A

35m^{2}+32m+5=0

35m^{2}+ 25m+ 7m+5=0

5m(7m +5) + 1(7m +5)=0

(7m+5) ( 5m+1)=0

m= -5/7 , -1/5

9n^{2}– 36n+32=0

9n^{2}-12n-24n +32=0

3n( 3n-4) -8(3n-4)=0

(3n-4) ( 3n-8)=0

n= 4/3, 8/3

Hence n>m - 35m
^{2}-18m-81=0

10n^{2}+184n-114=0m<nm<=nm>nm>=nthe relation cannot be determinedOption C

35m^{2}-18m-81=0

35m^{2}– 45m+ 63m-81=0

5m(7m -9) + 9(7m -9)=0

(7m-9) ( 5m+9)=0

m= 9/7 , -9/5

10n^{2}+184n-114=0

10n^{2}-6n+ 190n -114=0

n( 10n-6) + 19(10n-6)=0

(10n-6) ( n+19)=0

n= 6/10,- 19

Hence m>n - 10m
^{2}+79m+63=0

48n^{2}+10n-2=0m<nm<=nm>nm>=nthe relation cannot be determinedOption A

10m^{2}+79m+63=0

10m^{2}+70m+9m+63=0

10m(m +7) + 9(m +7)=0

(m+7) ( 10m+9)=0

m= -7 , -9/10

48n^{2}+10n-2=0

48n^{2}-6n+ 16n -2=0

6n( 8n-1) + 2(8n-1)=0

(8n-1) ( 6n+2)=0

n= 1/8, -2/6

Hence n>m - 2m
^{2}-35m= -17

2n^{2}+35n= +17m<nm<=nm>nm>=nthe relation cannot be determinedOption D

2m^{2}-35m= -17

2m^{2}-34m-1m+17=0

2m(m -17) -1(m -17)=0

(m-17) ( 2m-1)=0

m= 17 , 1/2

2m^{2}-35m= -17

2m^{2}-34m-1m+17=0

2m(m -17) -1(m -17)=0

(m-17) ( 2m-1)=0

m= 17 , 1/2

2n^{2}+35n= +17

2n^{2}+34n+1n+17=0

2n(n +17) +1(n +17)=0

(n+17) ( 2n+1)=0

n= -17 , -1/2

m>n

Hey! I just wish to give an enormous thumbs up for the nice data you have right here on this post. I shall be coming again to your blog for extra soon.